Analisis Abnormal Return dan Trading Volume Activity Sebelum dan Sesudah Ex-Dividend Date: Studi Kasus pada Perusahaan High Dividend 20 yang Terdaftar di Bursa Efek Inodnesia Tahun 2023 - Melia; Sahmin Noholo; Muliyani Mahmud (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to determine whether or not there are differences in abnormal returns and trading volume activity before and after the ex-dividend date in 20 high dividend companies listed on the Indonesia Stock Exchange in 2023. The type of method used in this research is a quantitative method. The sampling technique used was purposive sampling. There were 20 companies used as samples in the research. Research data taken for 30 days consists of 5 days, 10 days and 15 days before and after the ex-dividend date. The analysis used was the paired sample t-test and the Wilcoxon Signs rank test. Based on the research results, it shows that 1) there is no significant difference in abnormal returns before and after the ex-dividend date in high dividend 20 companies. 2) there is a significant difference in trading volume activity before and after the ex-dividend date in high dividend 20 companies.